The Effect Of Profitability, Liquidity, And Leverage On The Value Of Banking Sector Companies Listed On The Indonesia Stock Exchange (Idx) In 2022-2024 - Sofuli Zalukhu; Riska Franita (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the effect of profitability, liquidity, and leverage on firm value in the banking sector listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. The independent variables include profitability measured by Return on Assets (ROA), liquidity measured by the Current Ratio (CR), and leverage measured by the Debt to Equity Ratio (DER). The dependent variable is firm value, proxied by Tobin’s Q. The analytical methods used in this study include multiple linear regression, t-test, F-test, and the coefficient of determination, assisted by the SPSS software. The t-test results indicate that all independent variables have a partially significant effect on firm value. Profitability shows a t-value of 2.367 with a significance level of 0.016, liquidity shows a t-value of 2.232 with a significance level of 0.033, and leverage shows a t-value of 2.301 with a significance level of 0.003. These findings indicate that profitability, liquidity, and leverage individually contribute to increasing firm value. The F-test result shows an F-value of 5.509 with a significance level of 0.002, indicating that all independent variables simultaneously have a significant effect on firm value. The R Square value of 0.685 suggests that the three independent variables explain 68.5% of the variation in firm value, while the remaining percentage is influenced by other factors outside the research model.